Parkin Regulates the Activity of Pyruvate Kinase M2 - Liu, Kun; Li, Fanzhou; Han, Haichao; Chen, Yue; Mao, Zebin; Luo, Jianyuan; Zhao, Yingming; Zheng, Bin; Gu, Wei; Zhao, Wenhui (The Journal of biological chemistry, 2016)
Parkin, a ubiquitin E3 ligase, is mutated in most cases of autosomal recessive early onset Parkinson disease. It was discovered that Parkin is also mutated in glioblastoma and other human malignancies and that it inhibits tumor cell growth. Here, we identified pyruvate kinase M2 (PKM2) as a unique substrate for parkin through biochemical purification. We found that parkin interacts with PKM2 both in vitro and in vivo, and this interaction dramatically increases during glucose starvation. Ubiquitylation of PKM2 by parkin does not affect its stability but decreases its enzymatic activity. Parkin regulates the glycolysis pathway and affects the cell metabolism. Our studies revealed the novel important roles of parkin in tumor cell metabolism and provided new insight for therapy of Parkinson disease.